A test of inventory models with permissible delay in payment. Issue 4 (16th February 2017) - Seifert, Daniel; Seifert, Ralf W.; Isaksson, Olov H.D.
Abstract : Contrary to the long-standing view in the finance literature that firms should maximise payment delays, research in operations management suggests that long payment delays can be suboptimal. In this study, we reconcile these two views by applying a secondary data approach to established operations management theory. Based on a sample of 3383 groups of public US firms from a novel database, we find that our data are consistent with the causal relations and theoretical predictions of the operations management literature. Firm profitability is positively associated with payment delay. Payment delay, in turn, is positively associated with the capital cost difference between buyer and supplier and negatively associated with the price elasticity of demand and the deterioration rate of inventory. However, we do not observe any significant interaction effects between these factors, which raise a number of questions for future research.